Response of rice genotypes to bacterial leaf streak caused by Xanthomonas oryzae pv. oryzicola, an emerging threat in Nepal - Gupt, Shiwarttan Kumar; Pant, Khem Raj; Bastola, Biswash Raj (Fundamental and Applied Agriculture, 2021)
Bacterial leaf streak (BLS) is one of the devastating diseases of rice in Asia, Northern Australia, and West Africa that leads to up to 32% yield losses. Previously, BLS was rare in Nepal, but it has become more common in recent years, and it is supposed to cause signiﬁcant yield losses. However, studies on various aspects of BLS of rice, such as yield loss assessment, management strategy, germplasm evaluation, etc., have not been done in Nepal. Therefore, realizing the fact that the identiﬁcation of resistant genotypes is a cost-effective and efﬁcient approach to managing crop diseases; seventy-six rice genotypes were evaluated, along with resistant (Sabitri) and a susceptible (TN1) checks (usually used for bacterial leaf blight) under artiﬁcial epiphytotic conditions at the National Wheat Research Program (NWRP), Bhairahawa, Nepal, in the year 2018 and 2019. This study identiﬁed thirteen resistant and fourteen moderately resistant genotypes based on the mean percentage of disease severity over two years. The resistant genotypes viz., IR 108196-1-B-B-3-2-5, IR 10A 134, NR 2168-44-2-1-1-1-2-1-1, B 11598C-TB-2-1-B-7, IR 14D 198, IR 96279-39-3-1-2, IR 103587-22-2-3-B, BP 9474C-1-1-B, IR 10L 185, IR 15L 1735, IR 106529-20-40-3-2-B, IR 15D 1031 and IR 108541:12-27-1-3-B-B could be used as resistance sources in the breeding programs. Furthermore, resistant genotypes with high yield potential after evaluation across different environments could be released as BLS resistant varieties in Nepal. This study may be the ﬁrst effort to identify resistant rice geno- types, particularly against BLS, which is an emerging potential threat to rice production in Nepal.